New insights into fibrotic signaling in hepatocellular carcinoma - Shan, Liang; Wang, Fengling; Xue, Weiju; Zhai, Dandan; Liu, Jianjun; Lv, Xiongwen (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) mostly occurs in the background of liver fibrosis, and activated hepatic stellate cells (HSCs) exist in HCC tissues and adjacent tissues. HSC activation is involved throughout the development of HCC precancerous lesions, which has gradually attracted the attention of related researchers. In addition, HCC can promote the activation of HSCs, which in turn accelerates the occurrence and development of HCC by promoting tumor angiogenesis. In this review, we reviewed 264 studies from PubMed and ScienceDirect to summarize and analyze current significant fibrotic signaling in HCC. As a result, we found 10 fibrotic signaling pathways that are closely related to the activation, proliferation, invasion, migration, and promotion of apoptosis of HCC cells. In addition, we found that crosstalk between various fibrotic signaling pathways of HCC, hypoxia-induced energy metabolic reprogramming of HCC cells, matrix stiffness and stemness of HCC cells, and ferroptosis of HCC cells and HSCs are the latest research hotspots. Furthermore, related drugs that have been found to target these 10 fibrotic signaling pathways of HCC are listed. Our study provides a new reference for developing anti-HCC drugs.